2005
DOI: 10.1364/opex.13.008136
|View full text |Cite
|
Sign up to set email alerts
|

Slow light in a semiconductor waveguide at gigahertz frequencies

Abstract: We experimentally demonstrate slow-down of light by a factor of three in a 100 microm long semiconductor waveguide at room temperature and at a record-high frequency of 16.7 GHz. It is shown that the group velocity can be controlled all-optically as well as through an applied bias voltage. A semi-analytical model based on the effect of coherent population oscillations and taking into account propagation effects is derived and is shown to well account for the experimental results. It is shown that the carrier l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
162
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 0 publications
5
162
0
Order By: Relevance
“…In the practically important case where the input optical signal is a double-sideband signal generated by sinusoidal modulation of a laser beam, it can be shown that the refractive index dynamics plays no role in the observed phase shift [5]. The change in group velocity is in this case only controlled by the gain or absorption dynamics.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the practically important case where the input optical signal is a double-sideband signal generated by sinusoidal modulation of a laser beam, it can be shown that the refractive index dynamics plays no role in the observed phase shift [5]. The change in group velocity is in this case only controlled by the gain or absorption dynamics.…”
mentioning
confidence: 99%
“…This effect relies on the beating between two externally injected laser beams, or a single intensity-modulated laser beam with sidebands, which leads to oscillations of the electron density in the medium, which in turn alter the effective index seen by the optical signal. In general, the effect can therefore be described as a wave mixing phenomenon, where interactions between the frequency components are mediated by the complex susceptibility, which in semiconductor structures has contributions from various carrier dynamical processes [5], [6]. It has by now been experimentally demonstrated that light-speed control can be realized by CPO effects in a number of different semiconductor structures, i.e., bulk, quantum well (QW) or QD semiconductor optical amplifiers (SOAs) [6]- [10], electro absorbers (EAs) [5], and integrated SOA-EA pairs [11], [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, slow light in active semiconductor waveguides can provide very fast tuning speed, compact size, and low power consumption. [10][11][12][13] Though microwave phase shifts beyond 360 have been experimentally demonstrated, 13 fundamental limitations 11,14 make it difficult to achieve true time delays over a broad bandwidth, e.g., several tens of GHz, by using slow light effects.…”
mentioning
confidence: 99%
“…Hence, in the low-frequency range, the obtained time delay will be the same for the co-and counter-propagating configurations and is dominated by dynamical gain saturation effects. 14 …”
mentioning
confidence: 99%